Irritable bowel syndrome and vocational stress: individual psychotherapy - Patricia K Nel; H Gertie Pretorius; Anita D Stuart (AOSIS, 2003)
The goal of this study was to provide individualised psychotherapy for a sample suffering from IBS and vocational stress. Opsomming Die doelstelling van hierdie studie was om eïndividualiseerde psigoterapie te verskaf aan 'n steekproef van lyers met Prikkelbare Dermsindroom (PDS) en beroepspanning. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.